'We're all a bunch of nutters!': the production dynamics of Alternate reality games - Elizabeth, Evans (University of Southern California, Annenberg School of Communication and Journalism, 2014)
Alternate reality games (ARGs) combine transmedia and pervasive storytelling, layering fictional narratives onto real world spaces and raising a number of production challenges in the process. This article will consider the key professional skills, working attitudes, and relationships that sit behind ARGs’ complex narratives by focusing on a case study example, Nottingham-based The Malthusian Paradox (TMP). It will focus on how flexibility and trust were manifested throughout TMP’s production process and shaped the dynamics of the production team. In doing so, the article will argue that emerging transmedia narrative forms that exploit the potential of digital technologies are reshaping working practices within the creative industries and requiring practitioners to evolve and revaluate their roles within the creative process.